ORGANOLEPTIC ASSESSMENT AND PROXIMATE COMPOSITION OF SMOKED CATFISH Clarias gariepinus B. PRESERVED WITH THE ESSENTIAL OIL OF Ocimum gratissimum L. FROM EASTERN, NIGERIA - CHIBUKO, N. A; OSIBONA, A. O; NJOKU, d I. O. (Nigerian Journal of Fisheries, 2019)
This study focused on the analyses of essential oil extract of Ocimum gratissimum and evaluates the organoleptic and preservative properties as well as the proximate composition of smoked-dried catfish. The essential oil of Ocimum gratissimum was extracted using steam distillation and analysed using GC/MS. 31 components were detected which accounted for 100% of the oil. The oil was composed mainly of monoterpenes (58.06%), sesquiterpenes (49.94%). The different concentrations of the essential oils 0.25, 0.50, 0.75 and 1 ml preserved the fishes but 0.75ml improved the shelf-life of the fishes best. The sensory evaluation result obtained revealed the consumer’s tolerability of the essential oils as preservative and flavour enhancer for smoked Catfish in Nigeria.